Effectiveness of acceptance and commitment therapy in improving depression， anxiety， psychological flexibility and return-to-school rate among adolescents with school absenteeism - Zhang Yanshan; Chen Zhifang; Zheng Ke; Wu Guobang; Xu Fushan; Hu Maorong (Sichuan jingshen weisheng, 2025)
BackgroundThe issue of school absenteeism due to school refusal in adolescents has become increasingly prominent. Acceptance and Commitment Therapy （ACT） has been applied successfully to improve depression， anxiety， and psychological flexibility in adolescents， while few studies have tested the effect of ACT intervention on above-mentioned psychological aspects and return-to-school rate in adolescents with school absenteeism.ObjectiveTo explore the effect of ACT on depression， anxiety， psychological flexibility and return-to-school rate in school absenteeism adolescents， and to provide a broader evidence base for clinical interventions.MethodsFrom May to June 2024， a sample of 50 adolescents with Shenzhen school registration who had been suspended from school for more than a consecutive month for school refusal were recruited based on Wechat official account platform. The adolescents were divided into study group and control group by random number table method. Both groups received psychological education with the theme of 'Causes and Coping Strategies of School Refusal'， and study group added a 6-week ACT intervention with weekly 1-hour sessions. At baseline and after treatment， Patients’ Health Questionnaire Depression Scale-9 item （PHQ-9）， Generalized Anxiety Disorder Scale-7 item （GAD-7） and Comprehensive assessment of Acceptance and Commitment Therapy processes （CompACT） were used for the clinical evaluation.ResultsA total of 45 （90.00%）adolescents completed the study， including 25 in study group and 20 in control group. Analysis revealed that study group scored higher on PHQ-9 and GAD-7， while lower on total CompACT score， openness dimension and awareness dimension compared with control group， with statistical significance （F=7.786， 10.334， 12.922， 14.374， 3.075， P<0.05 or 0.01）. After intervention， the rate of return-to-school was higher in study group than in control group （40.00% vs 10.00%， χ²=5.114， P<0.05）.ConclusionACT intervention for adolescents with school absenteeism may alleviate depression and anxiety， improve their psychological flexibility and increase return-to-school rate.［Funded by the "14th Five Year Plan" for Social Sciences Project in Jiangxi Province （number， 24JY41D）； Science and Technology Planning Project of Shenzhen Municipality （number， 20210617155253001）］